Diagnosis of the causes of the deficiencies in listening and speaking skills in the English Teaching Learning process with students of Séptimo Año de Educación General Básica "F" at Unidad Educativa "Isabel de Godín", City of Riobamba, Chimborazo province, in the academic term February - July 2016. - Granda Castillo, Zoila Guadalupe (2017)
Learning is present in every single activity people perform around the world; however, the most of this learning is not deeply acquired or internalized. The present research consists of determining the causes of the deficiencies in listening and speaking skills of students at Unidad Educativa “Isabel de Godín”. It was noticed that a basic dialogue in English could not be held there. This study focuses on the diagnosis of the causes of the deficiencies in listening and speaking skills in the English Teaching-Learning process with students of seventh year of General Basic Education "F" in the academic term February-July 2016. The aim is to identify and describe the causes of those deficiencies, and then propose some solutions. This research is qualitative with the characteristics of field studies because it helps to explore, characterize and explain the causes of deficiencies in the use of oral skills based on information gathered from exactly where the problem arose and from the people involved in it; in addition to propose some possible solutions. This research is diagnostic, and the ethnographic method was used with its corresponding techniques such as: observation, interview, and survey, which were developed bearing in mind the research objectives and the scientific information regarding to the studied phenomenon, all of the above applied to the studied population. The deficiencies in listening and speaking skills are caused by some factors as it is shown in this investigation. Nevertheless, the most common factor is the lack of vocabulary that makes students unable to express their ideas in English. It is concluded for an effective development of the English skills to use a methodology that fosters the permanent interaction of students in real communication settings.